Intimate partner violence (IPV) in male and female orthopaedic trauma patients: a multicentre, cross-sectional prevalence study - Mohit Bhandari; Samantha Downie; Kim Madden; Iuliana Kanya; Arpit C Jariwala (BMJ Open)
Objectives Identify the proportion of patients attending fracture clinics who had suffered intimate partner violence (IPV) within the past year.Design Powered cross-sectional study using validated participant self-reported questionnaires.Setting and participants Adult trauma patients (no gender/age exclusions) attending one of three Scottish adult fracture clinics over 16-month period (from October 2016 to January 2018).Primary outcome measure Number of participants answering ‘yes’ to the Woman Abuse Screening Tool question: ‘In your current relationship over the past twelve months, has your partner ever abused you physically/emotionally/sexually?’Results Of 336 respondents, 46% (156/336 known) were women with 65% aged over 40 (212/328 known). The overall prevalence of IPV within the preceding 12 months was 12% 39/336) for both male and female patients. The lifetime prevalence of IPV among respondents was 20% (68/336). 38% of patients who had experienced IPV within the past 12 months had been physically abused (11/29). None of the patients were being seen for an injury caused by abuse. Two-thirds of respondents thought that staff should ask routinely about IPV (55%, 217/336), but only 5% had previously been asked about abuse (18/336).Conclusions This is the first study worldwide investigating the prevalence of IPV in fracture clinics for both male and female patients. 12-month prevalence of IPV in fracture clinic patients is significant and not affected by gender in this study. Patients appear willing to disclose abuse within this setting and are supportive of staff asking about abuse. This presents an opportunity to identify those at risk within this vulnerable population.